19 YEARS OLD WOMAN WITH TOXIC EPIDERMAL NECROLYSIS - Ikbal Sidiq (Fakultas Kedokteran Universitas Lampung, 2014)
Toxic Epidermal Necrolysis (TEN) is a syndrome that affects the skin, mucous membrane at the orifice, and eyes with severe general condition. The woman, 19 years old, came with the chief complaint of blisters on the skin with skin damage on the chest, neck, abdomen, back, groin, wrists, and feet for 4 days. Therapy specifically with systemic drugs ciprofloxacin 2x400 mg intravenously, 2x600 mg clindamycin intravenously, ceterizine 10 mg, and topical medications with NaCl 0.9% to compress the eyes and lips, andsilver sulfadiazine 1% cream. Toxic epidermal necrolysis diagnosis of patients based on the triad abnormalities of skin, mucosa, and eyes, as well as its relationship with the causes and laboratory investigations. [J Agromed Unila 2014; 1(3):274-276]Keywords: skin blister, toxic epidermal necrolysis, woman